Bridging The Gap in Vocational Training: A Needs Assessment of Personalized Learning for Life and Career Skills in Southern Thailand - Tanaphatsiri, Chaiya; Prasongchan, Piya (Journal of Technical Education and Training, 2026)
Driven by Industry 4.0 workforce demands, vocational education faces a critical challenge in aligning pedagogical practices with industrial needs. Grounded in Constructivist and Self-Regulated Learning theories, this study investigates the current and desired states of personalized learning management among vocational students in Southern Thailand and prioritizes the needs required to enhance essential life and career skills. Employing a quantitative needs assessment design, data were collected from 248 educational practitioners and administrators across 65 vocational colleges. The construct validity of the measurement instrument was rigorously verified through Confirmatory Factor Analysis (CFA). Data were analyzed using Paired-samples t-tests to establish inferential significance, alongside the Modified Priority Needs Index (PNImodified) to strategically rank critical areas for development. The findings reveal a highly significant disparity (p < .05) between the cumulative current state of personalized learning implementation (Mean = 19.49, SD = 2.04) and the desired future state (Mean = 27.51, SD = 2.51). The needs assessment identified the "Role of the Instructor" as the paramount priority (PNImodified = 0.44), underscoring an urgent mandate to transition from traditional lecturers to learning coaches. This was followed closely by the need for "Learning Assessment Skills" (PNImodified= 0.43), specifically prioritizing authentic and performance-based evaluation. The study confirms an urgent need for pedagogical transformation in technical and vocational education and training (TVET). By utilizing a robust needs assessment methodology, the findings provide a statistically validated, evidence-based framework for policymakers to prioritize human capital development specifically equipping instructors with coaching competencies and real-world assessment strategies to effectively bridge the skills gap.